BELON-BELON IMPIAN - Ahmad Naim Jaafar; Anizon Hussin; Mie Yeop (Shah Alam,Selangor: Perbadanan Perpustakaan Awam Selangor, 2023)
Achildren's story in Malay about dreams and aspiration,featuring colorful illustrationns
Keywords: Malaysian fiction(Malay); Chidren's stories; Malay fictions